Pemanfaatan Media Pembelajaran Interaktif dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadis di Madrasah Ibtidaiyah - Siti Waaqiah Khofidhotur Rofiah; Anas Tasya Dwi Qobayesi; Widya Duta Aulia; M. Ilmil Zawawi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This research is motivated by the low interest of students in learning the Qur'an and Hadith due to the dominance of conventional teaching methods that are considered less engaging. The study aims to examine the role of interactive learning media in increasing students’ learning motivation at Madrasah Ibtidaiyah. The research employs a qualitative literature study approach by collecting credible sources, including journal articles, textbooks, and previous research findings. Content analysis techniques were used to identify patterns, relationships, and important insights from the collected data. The findings indicate that interactive media such as educational videos, interactive animations, dynamic PowerPoint presentations, and digital quizzes significantly enhance students’ interest and motivation in learning. This improvement is reflected in higher levels of attention, curiosity, participation, and engagement during the learning process. In addition, the use of interactive media helps present Qur'an and Hadith concepts in a more concrete, attractive, and enjoyable way, thereby improving students’ understanding of the material. The study implies that integrating technology-based learning media can become an innovative strategy to optimize the teaching and learning process in Islamic elementary education institutions.